Improvement of Stability and Transdermal Delivery of Bioactive Compounds in Green Robusta Coffee Beans Extract Loaded Nanostructured Lipid Carriers. (10th May 2018) - Nitthikan, Nichcha; Leelapornpisid, Pimporn; Natakankitkul, Surapol; Chaiyana, Wantida; Mueller, Monika; Viernstein, Helmut; Kiattisin, Kanokwan
Abstract : The aim of this study was to develop green robusta coffee beans extract loaded nanostructured lipid carriers (NLCs) for enhancing dermal application and its efficiency. The green robusta coffee beans extract cultivated in Chumphon (CP) exhibited the highest antioxidant activity in the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay with IC50 of 34.1 ± 0.9 µ g/ml, lipid peroxidation inhibition with percentage inhibition of 38.8 ± 1.7, and ferric reducing antioxidant power (FRAP) assay with a FRAP value of 234.5 ± 12.3 mM FeSO4 /g. The extract contained caffeine, chlorogenic acid, and caffeic acid as major compounds. The anti-inflammatory test indicated that CP could decrease the secretion of IL-6 in macrophage cells and caused no irritation to blood vessels on the irritation test by hen's egg test chorioallantoic membrane (HET-CAM) assay. The particle size of CP-loaded NLCs was 158.1 ± 0.2 nm with a narrow polydispersity index and showed no noticeable difference after the stability test. Entrapment efficacy of CP-loaded NLCs was found to be over 60%. Caffeine and chlorogenic acid in CP-loaded NLCs were released sustainably and penetrated deeper into the skin than the extract in a conventional emulsion. In conclusion, the CP-loaded NLCs can be further used in cosmetics for dermal applications due to good efficacy and safety.